Physiological Changes and Blood Flow in Murrah Buffaloes during Summer and Winter Season - Upadhyay, R. C.; Kumar, Parveen; Kumar, Y.; Devi, Rajni; Singh, A. K. (Journal of Buffalo Science, 2014)
Present study was designed to investigate the changes in physiological reactions and blood flow during different seasons in Murrah buffaloes. Six Murrah buffalo heifers of 18-24 months were selected as experimental animals. The respiration rate (RR), heart rate (HR) and blood pressure was measured through BPL-Excello multi parameter monitor. Rectal temperatures were recorded with electronic thermometer. Skin surface temperatures at the different body sites were recorded using infrared thermometer (Metravi MT-2). The blood flow was measured on Perimed Multichannel Laser Doppler system using skin perfusion probe 408 at dorsal region, abdomen region and middle ear. Results showed a significant difference for respiration rate (P<0.001); rectal temperature (P<0.05) and heart rate (P<0.001) during summer and winter season. The mean blood pressure was 93.74/186.36 mmHg in summer and 97.40/198.08 mmHg in winter, respectively. In the present experiment, both diastolic and systolic pressure differed significantly (P<0.001) during different seasons. The mean skin surface temperature in summer was 37.03±0.39, 36.12±0.27 and 33.15±0.98°C at dorsal, abdomen and middle ear, respectively; whereas, during winter it was 29.87±0.69, 29.92±0.40 and 23.82±1.12°C at dorsal, abdomen and middle ear, respectively. The skin surface temperature among the different parts of the body differed significantly (P<0.001). During summer, the mean blood flow was 4.71±0.49, 14.85±1.63 and 16.72±1.47 PU; whereas, during winter, it was low, 1.10±0.16, 8.96±0.58 and 12.16±0.95 PU at dorsal, abdomen and middle ear, respectively. The difference in the blood flow among the different parts of the body differed significantly (P<0.001) in summer and winter. The results indicated that blood flow was positively correlated with temperature of the body parts and it varied in different seasons. This study concluded that, summer stress evokes a series of physiological changes in the Murrah buffalo’s, which affects production during summer season.